2022
DOI: 10.3390/proteomes10020020
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Gene Expression in Lymphoblasts from Parkinson’s Disease

Abstract: Parkinson’s disease is the second largest neurodegenerative disease worldwide and is caused by a combination of genetics and environment. It is characterized by the death of neurons in the substantia nigra of the brain but is not solely a disease of the brain, as it affects multiple tissues and organs. Studying Parkinson’s disease in accessible tissues such as skin and blood has increased our understanding of the disease’s pathogenesis. Here, we used lymphoblast cell lines generated from Parkinson’s disease pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Of note, a previous study reported a dramatically elevated basal mitochondrial respiration in iPD LCLs, which was observed independently of patient age, disease progression, and disease severity, suggesting an early and stable switch to a hyperactive state 56 . More recently, whole-cell transcriptomes and proteomes of iPD and healthy control LCLs showed downregulated transcripts for mitochondrial respiratory chain complexes but upregulated proteins, thereby suggesting that the elevated mitochondrial respiration observed in iPD LCLs is translationally regulated 57 . Interestingly, two studies performed in PRKN -mutant skin fibroblasts from PD patients also reported a higher mitochondrial respiratory rate compared to controls 58 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a previous study reported a dramatically elevated basal mitochondrial respiration in iPD LCLs, which was observed independently of patient age, disease progression, and disease severity, suggesting an early and stable switch to a hyperactive state 56 . More recently, whole-cell transcriptomes and proteomes of iPD and healthy control LCLs showed downregulated transcripts for mitochondrial respiratory chain complexes but upregulated proteins, thereby suggesting that the elevated mitochondrial respiration observed in iPD LCLs is translationally regulated 57 . Interestingly, two studies performed in PRKN -mutant skin fibroblasts from PD patients also reported a higher mitochondrial respiratory rate compared to controls 58 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Here, changes in translation could affect oxidative stress and the transport of neurotransmitters, thereby causing cells to be more susceptible to cell damage and death. In addition, a study on lymphoblasts generated from PD patients showed an overall downregulation of genes involved in protein synthesis ( Annesley et al, 2022 ). Thus, recent literature has shown that dysregulated synaptic translation and mitochondrial dysfunction are linked ( Kuzniewska et al, 2020 ), mitochondrial ribosomal proteins have been linked in a PD GWAS ( Billingsley et al, 2019 ), pathways related to ribosomes are enriched in an RNA-sequencing analysis of a PD cohort ( Hemmings et al, 2022 ), and that lymphoblasts generated from PD patients have dysregulated expression of genes involved in protein synthesis ( Annesley et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%